In vitro Plantlet Regeneration from Callus Culture of Trachyspermum copticum (Plant Tissue Culture and Biotechnology, 2017)
The effect of explant sources and plant growth regulators on callus induction and plantlet regeneration of Trachyspermum copticum were explored. Different explants including hypocotyl, cotyledonary node and leaf were cultured on MS supplemented with different combinations and concentrations of plant growth regulators including 2,4‐D (0.2‐3 0.5 mg/l), NAA (2 mg/l), BAP (1‐3 mg/l), Kn (0.5 mg/l) and IAA (0.8 mg/l). The best response for callus induction (100%) as well as quality was observed from cotyldonary node segments cultured on MS supplemented with 2, 4‐D at 1 mg/l in combination with Kn at 0.5 mg/l. Calli derived from various explants were subcultured on shoot induction media with different compositions and concentrations of medium. MS without any plant growth regulator promoted the highest frequency of shoot regeneration (100%) and also mean number of developed shoots per explants (3.8) showed the same result. Regenerated shoots were then rooted on three‐fourth strength MS with 75% efficiency after 30 days.Plant Tissue Cult. & Biotech. 27(1): 13-20, 2017 (June)